2015
DOI: 10.1007/s12010-015-1716-x
|View full text |Cite
|
Sign up to set email alerts
|

Semi-rational Directed Evolution of Monoamine Oxidase for Kinetic Resolution of rac-Mexiletine

Abstract: Semi-rational directed evolution was applied to the D5 variant of monoamine oxidase from Aspergillus niger (MAO-N-D5) with the aim of deriving the more desirable (R)-mexiletine through the kinetic resolution of mexiletine enantiomers. Although MAO-N-D5 shows no activity towards rac-mexiletine, theoretical molecular docking studies revealed the potential binding conformations of both mexiletine enantiomers and MAO-N-D5. The key factors affecting the catalytic activity and specificity were identified. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…They found a small difference between the (1R,2S) and (1S,2R) enantiomers, and concluded that racemic cis -cyclopropylamines can be used for the experimental work based on the lack of enantiomeric differences obtained by using docking. In other work, Chen et al [ 29 ] used docking (AutoDock) to study the interactions between mexiletine enantiomers and the D5 variant of monoamine oxidase from Aspergillus niger (MAO-N-D5). They found that the calculated binding energies of (R)-mexiletine and (S)-mexiletine with MAO-N-D5 were −5.91 and −6.84 kcal/mol, respectively, which indicates that MAO-N-D5 binds and reacts preferentially with (S)-mexiletine.…”
Section: Docking Binding Energy Predictions For Enantiomeric Drugsmentioning
confidence: 99%
“…They found a small difference between the (1R,2S) and (1S,2R) enantiomers, and concluded that racemic cis -cyclopropylamines can be used for the experimental work based on the lack of enantiomeric differences obtained by using docking. In other work, Chen et al [ 29 ] used docking (AutoDock) to study the interactions between mexiletine enantiomers and the D5 variant of monoamine oxidase from Aspergillus niger (MAO-N-D5). They found that the calculated binding energies of (R)-mexiletine and (S)-mexiletine with MAO-N-D5 were −5.91 and −6.84 kcal/mol, respectively, which indicates that MAO-N-D5 binds and reacts preferentially with (S)-mexiletine.…”
Section: Docking Binding Energy Predictions For Enantiomeric Drugsmentioning
confidence: 99%
“…Similar observation was indicated for the two thiocarbazate enantiomers of cathepsin L. Molecular docking studies revealed the docking score of S-enantioner (9.03 kcal/mol) more than the R-enantiomer (7.02 kcal/mol), the difference was also validated in their biological activity; S-enantiomer, with an IC50 of 56 nM and R-enantiomer, with an IC50 of 33 μM [128]. The importance of enantiomerism in the interaction of compounds with their binding sites, evaluated by docking scores, was also mentioned in other works [129,130]. On the basis of the earlier reports, it can be accepted that endoribonuclease has shown a better binding affinity for one enantiomer than the other in the present molecular docking study.…”
Section: Discussionmentioning
confidence: 69%
“…Directed evolution can promote the enzymatic activity of lipase, xylanase, a-galactosidases, monoamine oxidase and nitrilase [14][15][16][17][18][19]. L-tryptophan and S-phenyl-L-cysteine were synthesized by tryptophan synthase of Escherichia coli k-12, and it was found that tryptophan synthase has the potential to synthesize L-tryptophan and its derivatives [20][21][22].…”
Section: Introductionmentioning
confidence: 99%